The effect of competence,communication,work ethic and work motivation on employee performance of the Sungai Penuh City Education Office - Yannizar, Yannizar; Mutiawati, Mutiawati; Satrio, Satrio; Novita, Dien (Jurnal Mantik, 2024)
This study aims to see the effect of competence, communication, work ethic and motivation both partially and simultaneously on employee performance at the Sungai Penuh City Education Office. The population in this study were all employees at the Sungai Penuh City Education Office as many as 45 people. And this sampling technique uses total sampling technique (overall sample). The data analysis technique is multiple linear regression using the classical assumption tests of normality, multicollinearity, and heteroscedasticity. The results of this study indicate that competence has a positive effect on employee performance at the Sungai Penuh City Education Office. Communication has a positive influence on employee performance at the Sungai Penuh City Education Office. Work Ethic has a positive influence on employee performance at the Sungai Penuh City Education Office. Motivation has a positive influence on employee performance at the Sungai Penuh City Education Office. Competence, communication and work ethic, motivation together have a positive effect on employee performance at the Sungai Penuh City Education Office.